(untitled) (Research, Society and Development, 2022)
The aim of this study was to conduct a systematic review of the literature on Burnout Syndrome in first-responder professionals in the Covid-19 pandemic in Brazil. For this, PMC, PUBMED, BVS and Scielo databases were searched, according to the PRISMA methodology. Out of the 738 studies located, two met the inclusion criteria. Physical and emotional exhaustion were identified in the studies, along with the prevalence of signs and symptoms of the Burnout Syndrome. The evidence, albeit still scarce, points to exhaustion of these professionals. Strategies to manage or identify possible signs and symptoms related to mental health suffering at work are necessary.